The Experience of Using a Shariah-Compliant Homestay Accommodation Facility Service in Sabah: From The Perspective of a Tourist or Guest - Suhailah Abdul Muin; Mohd. Nor Azan Abdullah; Norcikeyonn Samuni (Universiti Sains Islam Malaysia, 2024)
Ulum Islamiyyah, Volume 36 Issue 02 Page (127–138)